More on the Energy/Non-Energy Price Link - Baffes, J. (2012)
This note re-examines the energy/nonenergy price link. Using annual data from the period 1960 to 2008, it finds that the pass-through of energy price changes to the overall nonenergy commodity index is 0.28. At a more disaggregated level, the fertilizer index exhibited the largest pass-through (0.55), followed by agriculture (0.26) and metals (0.25).